Commissioning and verification of the collapsed cone convolution superposition algorithm for SBRT delivery using flattening filter‐free beams. (6th March 2014) - Foster, Ryan D.; Speiser, Michael P.; Solberg, Timothy D.
Abstract : Linacs equipped with flattening filter‐free (FFF) megavoltage photon beams are now commercially available. However, the commissioning of FFF beams poses challenges that are not shared with traditional flattened megavoltage X‐ray beams. The planning system must model a beam that is peaked in the center and has an energy spectrum that is softer than the flattened beam. Removing the flattening filter also increases the maximum possible dose rates from 600 MU/min up to 2400 MU/min in some cases; this increase in dose rate affects the recombination correction factor, P ion, used during absolute dose calibration with ionization chambers. We present the first‐reported experience of commissioning, verification, and clinical use of the collapsed cone convolution superposition (CCCS) dose calculation algorithm for commercially available flattening filter‐free beams. Our commissioning data are compared to previously reported measurements and Monte Carlo studies of FFF beams. Commissioning was verified by making point‐dose measurement of test plans, irradiating the RPC lung phantom, and performing patient‐specific QA. The average point‐dose difference between calculations and measurements of all test plans and all patient specific QA measurements is 0.80%, and the RPC phantom absolute dose differences for the two thermoluminescent dosimeters (TLDs) in the phantom planning target volume (PTV) were 1% and 2%, respectively. One hundred percent (100%) of points in the RPC phantom films passed the RPC gamma criteria of 5% and 5 mm. Our results show that the CCCS algorithm can accurately model FFF beams and calculate SBRT dose distributions using those beams. PACS number: 87.55.kh